2021
DOI: 10.3389/fimmu.2021.612846
|View full text |Cite
|
Sign up to set email alerts
|

A Clot Twist: Extreme Variation in Coagulotoxicity Mechanisms in Mexican Neotropical Rattlesnake Venoms

Abstract: Rattlesnakes are a diverse clade of pit vipers (snake family Viperidae, subfamily Crotalinae) that consists of numerous medically significant species. We used validated in vitro assays measuring venom-induced clotting time and strength of any clots formed in human plasma and fibrinogen to assess the coagulotoxic activity of the four medically relevant Mexican rattlesnake species Crotalus culminatus, C. mictlantecuhtli, C. molossus, and C. tzabcan. We report the first evidence of true procoagulant activity by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 144 publications
1
16
0
Order By: Relevance
“…The comparative testing of the enzyme inhibitors prinomastat and DMPS revealed highly contrasting differences in their specific abilities to neutralize the P-IIId SVMP responsible for FX activation by the venoms in this study. This is congruent with recent data published for FX activation of neonate Crotalus culminatus venom, which prinomastat neutralised but DMPS at the same concentration did not ( 59 ) and another report of DMPS requiring long incubation times to exert a discernable effect ( 60 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The comparative testing of the enzyme inhibitors prinomastat and DMPS revealed highly contrasting differences in their specific abilities to neutralize the P-IIId SVMP responsible for FX activation by the venoms in this study. This is congruent with recent data published for FX activation of neonate Crotalus culminatus venom, which prinomastat neutralised but DMPS at the same concentration did not ( 59 ) and another report of DMPS requiring long incubation times to exert a discernable effect ( 60 ).…”
Section: Discussionsupporting
confidence: 92%
“…Such variation in relationship to altitude and prey type and prey escape potential has been noted for the rattlesnake species Crotalus helleri ( 79 ). In addition, as all venom samples used in this study from adult specimens, future work should examine ontogenetic shifts to ascertain if juvenile snakes have differentially procoagulant venoms, which has been noted for other species ( 59 , 78 , 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected and hints at different levels of drug exposure and metabolism in this single dose intravenous-delivered model, as both matrix metalloproteinase inhibiting drugs showed potent inhibitory activity in our in vitro assays and have been shown in other studies to neutralise the in vivo lethal effects of E. ocellatus venom in murine models ( Arias et al, 2017 ; Albulescu et al, 2020a ). Studies by other groups have similarly shown the impressive in vitro inhibitory activities of marimastat and prinomastat against SVMP activity in rattlesnakes and a wide range of palearctic vipers ( Chowdhury et al, 2021a ; Seneci et al, 2021 ) and strong inhibitory effects of prinomastat against the anticoagulant activity of spitting cobra venoms ( Chowdhury et al, 2021b ).…”
Section: Discussionmentioning
confidence: 89%
“…12 ). Clotting factor activation has also been documented in the additional crotaline genera Calloselasma (Factor X) and Crotalus (Factor X by neonate Crotalus culminatus ) [ 116 , 117 ], but the toxins responsible have not been sequenced. Consequently, their phylogenetic affinity to the Bothrops -type procoagulant P-III SVMP is unknown, and it cannot be determined whether procoagulant SVMPs have evolved once or several times in the pit vipers.…”
Section: Resultsmentioning
confidence: 99%